PENGIRIMAN TENAGA KERJA INDONESIA (TKI) KE MALAYSIA MELALUI KOTA SEMARANG - Irwan Pasetia (PIRAMIDA, 2008)
This article discussing about Indonesian’s labor. Many out of workersused the special way that was supplied by Government; the legalization ofrequirement agency was showed by Government. It was called the servicemobilization of Indonesian’s labor (Pengerah Jasa Tenaga Kerja Indonesia). Butthe requirement process and the place process of Indonesian’s labor were alwaysas disadvantages side. Many problems of the cost that have to be guaranteed byIndonesian’s labor candidates before they went to abroad. The law of enforcementto guarantee safety of Indonesian’s labor has not been priority yet. According tothe quantity, Semarang city sent many Indonesian’s labor to Malaysia. Thispurposes of this article are; 1) to describe the processing of sending managementIndonesian’s labor to Malaysia by Semarang’s PJTKI.2) to explain Indonesian’slabor interaction toward PJTKI and Government sent Indonesian’s labor toMalaysia by Semarang City. 3) To know the sending effects of Indonsian’s laborto Malaysia by Semarang’s PJTKI. According to the article result could beconcluded that Indonesian’s labor of Semarang has ever worked or will work toMalaysia that the age and education were contradiction to Government rule.Beside that, the sending process of Indonesian’s labor to Malaysia, either predeparture,placement, or return. It was still difficult and the deflection. BeingLegal Indonesian’s labor was more difficult and very bureaucratic that illegal –way.